The Relationship between Clinical Appearance and Albumin Levels in Pulmonary Tuberculosis (TB) Patients at Dr. M. Djamil General Hospital, Padang, Indonesia - Afriani Afriani; Masrul Basyar; Yulia Helexandra (HM Publisher, 2023)
Background: Pulmonary TB is strongly associated with malnutrition. Malnutrition is often found in pulmonary TB patients, especially hospitalized patients, and can worsen the treatment and recovery outcomes of pulmonary TB patients. Pulmonary TB patients can experience a significant decrease in albumin levels, and albumin is the largest protein in blood plasma. This study aimed to determine the relationship between the patient's clinical appearance and albumin levels in pulmonary tuberculosis patients at Dr. M. Djamil General Hospital, Padang, Indonesia. Methods: This study was an analytic observational study with a retrospective cohort approach. A total of 177 research subjects participate in this study. Observations on sociodemographic data, clinical data, and laboratory data were carried out in this study. Data analysis was carried out using SPSS version 25 univariate and bivariate. Results: Clinical appearance of pulmonary TB patients treated in the pulmonary ward isolation room at Dr. M. Djamil General Hospital, Padang, Indonesia, which is significantly related to albumin levels is BMI (underweight and normal) and complications pneumothorax (p<0.05); while other clinical appearances such as onset and complications of coughing up blood, pleural effusion, hydropneumothorax, and without complications not related to albumin levels (p>0.05). Conclusion: BMI (underweight and normal) and complications pneumothorax is a clinical picture related to albumin levels in pulmonary tuberculosis patients at Dr. M. Djamil General Hospital, Padang, Indonesia.